2022
DOI: 10.2298/pac2202183z
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of large-sized thin architectural ceramic plate enhanced by alumina fibres and in situ mullite whiskers

Abstract: The fibres reinforced thin architectural ceramic plates of 900?1800?2.5mm with excellent mechanical properties were prepared by fast-sintering method using a controllable fibre dispersion process. The effects of ball-milling time on dispersity, average length-to-diameter ratio and microstructure of alumina fibres were investigated. Meanwhile, the effects of alumina fibre contents on the bulk density, water absorption, phase transformation and microstructure of the thin ceramic plate were rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Various strategies have been proposed to enhance the mechanical properties of these ceramics, such as adding fibers and reinforcement phases, but most are too expensive and challenging to integrate into ceramic industries. [7][8][9] Zhong et al 10 demonstrated the effective improvement of mechanical properties for ceramic tiles using in situ mullite whiskers. Xiao et al 11 found that in situ mullite whiskers could be generated by strictly controlling the raw material ratio, making them suitable for preparing high-strength ceramic tiles in industrial manufacturing.…”
Section: Introductionmentioning
confidence: 99%
“…Various strategies have been proposed to enhance the mechanical properties of these ceramics, such as adding fibers and reinforcement phases, but most are too expensive and challenging to integrate into ceramic industries. [7][8][9] Zhong et al 10 demonstrated the effective improvement of mechanical properties for ceramic tiles using in situ mullite whiskers. Xiao et al 11 found that in situ mullite whiskers could be generated by strictly controlling the raw material ratio, making them suitable for preparing high-strength ceramic tiles in industrial manufacturing.…”
Section: Introductionmentioning
confidence: 99%